2020
DOI: 10.1002/marc.202000463
|View full text |Cite
|
Sign up to set email alerts
|

Catalyst‐Free Multicomponent Cyclopolymerizations of Diisocyanides, Activated Alkynes, and 1,4‐Dibromo‐2,3‐Butanedione: a Facile Strategy toward Functional Polyiminofurans Containing Bromomethyl Groups

Abstract: Polymers containing iminofuran (PIFs) are rarely reported due to the lack of simple and effective synthesis methods. In this work, a novel multicomponent cyclopolymerization (MCCP) of diisocyanides, activated alkynes, and 1,4‐dibromo‐2,3‐butanedione using catalyst‐free one‐pot reactions under mild conditions to prepare PIFs containing bromomethyl groups is reported. PIFs with good solubility and thermal stability are obtained with high Mws (up to 19 600) and good yields (up to 89.5%) under optimized polymeriza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 59 publications
1
14
0
Order By: Relevance
“…The results demonstrated that the bis-spiropolymers synthesized from nonaromatic monomers 1a and 1b showed emission peaks ranging from 500 to 550 nm, which should result from cluster-triggered emission characteristics caused by the ester groups according to our previous work. [44,55] The polymers P1c3a and P1c3b based on aromatic monomer 1c, however, www.advancedsciencenews.com www.mrc-journal.de showed no emission, which is attributed to the poor throughspace conjugation. [56,57]…”
Section: Photophysical Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The results demonstrated that the bis-spiropolymers synthesized from nonaromatic monomers 1a and 1b showed emission peaks ranging from 500 to 550 nm, which should result from cluster-triggered emission characteristics caused by the ester groups according to our previous work. [44,55] The polymers P1c3a and P1c3b based on aromatic monomer 1c, however, www.advancedsciencenews.com www.mrc-journal.de showed no emission, which is attributed to the poor throughspace conjugation. [56,57]…”
Section: Photophysical Propertiesmentioning
confidence: 99%
“…Due to the bis-spirorings with halogen and UV-sensitive iminofuran rings in the obtained polymers, [44] the bis-spiropolymers could be used in the pesticide field by degradation. UV-vis absorption spectra were used to characterize the photodegradation process of P1a3c as an example under simulated sunlight at 380-780 nm (Figure S27, Supporting Information).…”
Section: Photosensitizer Induced Degradation Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Dong's group has also made great contributions for the in-situ construction of five-membered heterocyclic polymers based on isonitriles. [37][38][39][40][41][42][43] For example, they reported a catalystfree cyclopolymerization of diisocyanide, dialkylacetylene dicarboxylates and dialdehyde in 2019 (Scheme 2C). [42] The reaction in situ generated poly(amine-furan-arylene)s with high molecular weights (M w up to 76 400 g mol −1 ) and good thermal stability under mild conditions.…”
Section: Scheme 2cmentioning
confidence: 99%
“…Very recently, Dong's group further expanded the polymerization routes toward the furan-derivative polymers by a cyclopolymerization of diisocyanides, activated alkynes and 1,4-dibromo-2,3-butanedione (Scheme 2D). [43] This catalyst-free polymerization efficiently produced five-membered heterocyclic polymers containing post-functionalizable bromomethyl group. The M w of the polymeric products was up to 19 600 g mol −1 .…”
Section: Scheme 2cmentioning
confidence: 99%